Pathophysiology and Epidemiology of Diverticular Disease - Talutis, Stephanie D.; Kuhnen, F Angela H. (Clinics in Colon and Rectal Surgery, 2020)
Diverticular disease exists on a spectrum, ranging from asymptomatic diverticulosis to complicated diverticulitis. Incidence of diverticulitis in western nations has increased in recent years, although the factors that influence the progression from diverticulosis to diverticulitis are unknown. Geographic/environmental influences, lifestyle variables, and microbiota of the gastrointestinal tract are some of the factors implicated in diverticular disease.
Keywords: diverticulitis; diverticulosis; colon; inflammation; risk factors; microbiome